The water balance in Rio Grande do Sul State, Brazil - Mota, Fernando Silveira da (2014)
A study of the water balance in Rio Grande do Sul, Brazil, was made to give a climatological basis for the solution of serious problems of the regional agriculture. Summer droughts, excess rainfall in winter, spring and fall, and tremendous year-to-year variability in total rainfall are examples of these problems. Due to the work of Ladislau Coussirat de Araujo, started in 1910, the State of Rio Grande do Sul has a very well distributed climatological network, with more than 40 years of continuous and uniform observations. These data made the present study possible. The great contribution of C.W. Thornthwaite's methods for the study of the water balance was used here for analysis of the Rio Grande do Sul data. The concept of potencial evapotranspiration is discussed and its method of calculation as well as those for the water balance are presented. The State of Rio Grande do Sul may be divided into three zones corresponding to three distinct types of water balance. In the south, there is a dry season, a season of soil moisture recharge and one of water surplus. A certain amount of water, stored from previous rains, is used during the dry season, but this is not enough to meet the water needs. The dry season, of 1 to 4 months duration depending on the region considered, begins in the spring and continues through the summer in the driest localities. During the initial period of soil moisture recharge, beginning in Autumn, the rains are greater than the potential evapotranspiration, but the difference is not enough for the saturation of the soil and hence a water surplus does not occur. The water surplus season occurs during the interval from late autumn to early spring. This type of water balance also occurs in a restricted zone around Marcelino Ramos, in the northern part of the state. In the central area of the state (São Gabriel, São Luiz Gonzaga, Santiago, Santa Cruz, Caçapava, etc.) there is a season in which moisture needs are not met by rainfall but are met by soil moisture stored during the preceding period. This season during which supplemental moisture requirements are met from residual soil moisture occurs in late spring and early summer. Following this, soil moisture recharge occurs and saturation of storage capacity is reached by the end of summer. From late summer to early spring precipitation is in excess of storage capacity of the soil. Both in this central zone as well as the entire state, the rainy season has two maxima, one in May-June and the other in August-September. A type of moisture regime, normally without a true dry period, but in which stored water is utilized also occurs along the northern coast of Rio Grande do Sul (Torres). In the northern area of the state, especially in the Planalto, there normally is no dry season, excess precipitation occurring all months of the year. Examples of year-to-year variations in deficiencies and excesses of moisture are given and attention is called to their economic importance. These variations are shown in four graphs. The so-called invisible droughts in reality correspond to the types of hydrologic patterns prevailing in the state. Means of controlling the effects of deficiencies and excess of water are discussed, with attention directed to need for expansion of solutions already in use (dams for irrigation, drainage, erosion control, forage reserves, cattle shelters, etc.). In twelve maps, data showing geographic distribution of potential and actual evapotranspiration and of water deficits and excesses by season are presented. Seasonal variations of these data are shown in 15 graphs.